2002
DOI: 10.1556/amicr.49.2002.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes, virulence factors, antibiotic sensitivity, beta-lactamase activity and plasmid analysis of Salmonella from children with diarrhea in Tripoli (Libya)

Abstract: A total of 21 Salmonella strains isolated in Libya (16 from children with diarrhea and 5 from healthy controls) were serotyped and studied for their cell invasive ability, production of cytotoxin, antibiotic susceptibility, beta-lactamase activity and plasmid profiles. Eight different serotypes of Salmonella were identified: 6 S. saintpaul, 4 S. wien (1 from control), 2 S. newport, 2 S. muenchen (1 from control), 2 S. typhimurium (1 from control), 2 S. hadar (1 from control), 2 S. reading (1 from control), 1 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…48,49 High rates of resistance to multiple antimicrobial agents (resistance to three or more classes of antibiotics) by enteric pathogenic were previously reported from Libya. 12,50,51 Similarly, a high percentage of multiple-drug-resistance was identified among the bacterial pathogens examined in this work. Moreover, we found almost two-thirds of Salmonella isolates were resistant to ciprofloxacin, a rate that was unexpected because previous studies from Libya reported fluoroquinolones susceptibility of all salmonellae isolated from diarrheic children.…”
Section: Diarrhea In Libyan Childrensupporting
confidence: 53%
See 1 more Smart Citation
“…48,49 High rates of resistance to multiple antimicrobial agents (resistance to three or more classes of antibiotics) by enteric pathogenic were previously reported from Libya. 12,50,51 Similarly, a high percentage of multiple-drug-resistance was identified among the bacterial pathogens examined in this work. Moreover, we found almost two-thirds of Salmonella isolates were resistant to ciprofloxacin, a rate that was unexpected because previous studies from Libya reported fluoroquinolones susceptibility of all salmonellae isolated from diarrheic children.…”
Section: Diarrhea In Libyan Childrensupporting
confidence: 53%
“…Moreover, we found almost two-thirds of Salmonella isolates were resistant to ciprofloxacin, a rate that was unexpected because previous studies from Libya reported fluoroquinolones susceptibility of all salmonellae isolated from diarrheic children. 12,50 Although nalidixic acid and ciprofloxacin are not used routinely in the treatment of childhood infectious diarrhea in Tripoli hospitals (Dr. Suhila O. Almbrok, Al-Jala Children Hospital, Tripoli, personnel communication), this finding represents a serious health problem because fluoroquinolones are the drugs of choice in the treatment of salmonellosis and other infectious syndromes (e.g., urinary tract infections) in adults; in particular, a high rate of resistance to ampicillin and trimethoprim-sulphamethoxazole is observed among isolates recovered. 52 -54 Ciprofloxacin is licensed for use both in animals and humans in some developing countries and in Libya antimicrobials, including the fluoroquinolones, are available to the public without the need for medical prescription.…”
Section: -26mentioning
confidence: 99%
“…During the period 1990–1999, more than 40% of Salmonella and Shigella from children with diarrhea were resistant to ampicillin and trimethoprim-sulfamethoxazole (3, 8). Similar findings were reported for Salmonella from Benghazi (4).…”
Section: Salmonella and Shigellamentioning
confidence: 99%
“…According to the Information System of Public Health Laboratory in USA (1968USA ( -1998, the mean number of cases of human salmonellosis was 43 per year and in 2001 Salmonella Kottbus infection was observed in 23 people who had eaten alfafa sprouts (CENTER OF DISEASE CONTROL AND PREVENTION, 2002). In Lybia, a multi-drug resistant strain of S. Kottbus was among 21 Salmonella strains isolated from 16 children with diarrhea (El_Ghodban et al, 2002). According to Nelius et al (1969), most Salmonella infections remain as enteric diseases, however, S. Kottbus may cause septicemia that is often related to immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%